Etnomathematic Exploration Study on The Traditional Dance of Kethek Ogleng - Asriyanto, Amrih Mulat Arif; Muhibbin, Ahmad; Widyasari, Choiriyah; Prastiwi, Yeny; Ramawati, Laili Etika (Universitas Pendidikan Ganesha, 2022)
Learning in elementary school is more interesting when learning with the culture that surrounds students. This study aims to explore the ethnomathematical content of the traditional dance of Kethek Ogleng. This study uses qualitative research with an ethnographic approach. Data collection techniques by observation, documentation, and interviews. The data analysis technique used is Domain Analysis and Taxonomy. The analysis steps obtain a general picture and a comprehensive concept of the object then into a concept. The result of the research is that the ethnomathematical content in the traditional dance of Kethek ogleng consists of, first, the concept of a circular flat shape, this concept is present when the dancer performs a knuckle movement. Second, build a tube room, which is found on drums as a dance accompaniment. Third, the angle is found in the curve of the foot when the dancer makes a dreamy movement. Fourth, there is a time limit on the duration of the dancer's performance. Fifth, the concept of a flat, square shape, is found in the dancer's pants decoration. The conclusions of this study prove that the traditional Kethek Ogleng dance originating from Wonogiri contains ethnomathematics. Therefore, this traditional tariff can be used as a medium for making learning designs for elementary school children.